Production of Recombinant Proline Dehydrogenase Enzyme from Pseudomonas fluorescens pf-5 in E. coli System - E. Omidinia (Journal of Sciences, Islamic Republic of Iran)
Proline dehydrogenase (ProDH; 1.5.99.8) belongs to superfamily of amino acid dehydrogenase, which plays a significant role in the metabolic pathway from proline to glutamate. The goal of this research was gene cloning and characterization of ProDH enzyme from Pseudomonas fluorescens pf-5 strain. The gene encoding ProDH was isolated by means of PCR amplification and cloned in an IPTG inducible T7-based expression system. The Histidine-tagged recombinant enzyme was purified and its kinetic properties were studied. According to SDS-PAGE analysis ProDH revealed a MW of 40 kDa. The Km and Vmax values of P. fluorescens ProDH were estimated to be 20 mM and 160 ?mol/min, respectively. ProDH activity was stable at alkaline pH and the highest activity was observed at pH 8.5 and 30°C. This study is the first data on the isolation and production of P. fluorescens ProDH enzyme in E. coli expression system.